Prosodic Marking of New and Given Information in English and Mandarin by Chinese Speakers - Jiang, Man (Journal of Modern Languages, 2023)
Second-language speakers have been found to face difficulties marking prosodic features of new and given information in English. Chinese English as a Foreign Language (EFL) learners speak English with a different intonation from L1 speakers, which can lead to misunderstanding. However, there is a dearth of research on the prosodic marking of new and given information by Chinese English speakers and on the extent to which Mandarin might influence the marking of new and given information. To fill this research gap, an empirical study of the prosodic features of English and Mandarin was conducted using a combination of qualitative and quantitative research methods to investigate the prosodic marking of new and given information in English and Mandarin by Chinese speakers. The results show that the prosodic marking of new and given information in English and Mandarin was similar with new information having a longer duration and a larger pitch range.